Мигель Де Сервантес Сааведра ба монгол уншигчид: Miguel De Cervantes Saavedra and mongolian readers - D., Galbaatar; G., Galbayar (Mongolian Journal of Foreign Languages and Cultures, 2023)
Miguel de Cervantes is one of the world’s pre-eminent novelists and the most celebrated figure in Spanish Renaissance literature. His life corresponds to the blend of high adventure and grim reality that shaped his masterpiece. His works have served as an illuminating mirror for each age that pick it up. His most renowned work is “Don Quixote”, regarded as a world’s classic literature. The value of any literary creation is in its artistry. Artistically, the tradition and development of the novel, as well as its central concerns of human psychology and social satire, the question of human identity, and the interplay of the artist between the real and the imagined, can all be traced directly to life of Cervantes. In our opinion, the picaresque adventures of the mad Quixote and his ‘impossible dream’ and victory of reason and fact over fancy and idealism exhort the readers which makes “Don Quixote” as a stimulating novel. “Don Quixote” has been translated, in full, into Mongolian in 1972 and it represented broadly in art and drama.